Comprehensive Physiology 2017
DOI: 10.1002/cphy.c160021
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Fundamentals of Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) was first recognized more than four decades ago and occurred independent of cardiovascular diseases or hypertension in both type 1 and type 2 diabetic patients. The exact mechanisms underlying this disease remain incompletely understood. Several pathophysiological bases responsible for DCM have been proposed, including the presence of hyperglycemia, nonenzymatic glycosylation of large molecules (e.g., proteins), energy metabolic disturbance, mitochondrial damage and dysfunction, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 247 publications
0
95
0
1
Order By: Relevance
“…DCM results in a high-risk of heart failure, arrhythmia and sudden death, and is the major cause of mortality in patients with diabetes [3,4]. The pathogenesis of DCM includes altered metabolism, mitochondrial dysfunction, oxidative stress, inflammation, cell death and remodeling of the extracellular matrix [5]. However, the diagnosis and therapy of DCM are limited because the molecular mechanisms of DCM remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…DCM results in a high-risk of heart failure, arrhythmia and sudden death, and is the major cause of mortality in patients with diabetes [3,4]. The pathogenesis of DCM includes altered metabolism, mitochondrial dysfunction, oxidative stress, inflammation, cell death and remodeling of the extracellular matrix [5]. However, the diagnosis and therapy of DCM are limited because the molecular mechanisms of DCM remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…DM is characterized by high blood glucose and leads to multiple complications including diabetic retinopathy, diabetic nephropathy, and diabetic neuropathy (Baba and Ishizaki, 1992;Chen et al, 2017;Hung et al, 2017;Ung et al, 2017). Of these, DCM is a major complication, causing high morbidity and mortality (Frati et al, 2017;Gilca et al, 2017;Hu et al, 2017). Evidence indicates that Chinese traditional medicine and phytomedicine have beneficial effects on diabetic complications including DCM.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous deepening of diabetes research, people's research on diabetes and its complications has entered the genetic level. More and more studies have shown that noncoding RNA (ncRNA) plays a vital role in the occurrence and development of DCM . For example, microRNAs (miRNAs, miRs) play an essential role in the incident and development of DCM .…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…The typical morphological features of apoptosis are DNA fragmentation, rounding of cell shrinkage, condensation of chromatin, vacuolation of the membrane, nuclear condensation, and small apoptosis. The signal transduction pathways are mainly intrinsic pathways, also known as mitochondrial pathways; exogenous pathways, also known as death receptor pathways; and ER pathways . Autophagy is an active process of cell death mediated by cellular signalling pathways.…”
Section: The Possible Mechanism Of Lncrna In Dcmmentioning
confidence: 99%
See 1 more Smart Citation